PENGENALAN TANAMAN MULTIGUNA MELALUI KEGIATAN PEMBERDAYAAN MASYARAKAT DI DUSUN BANGKO, DESA DODINGA, HALMAHERA BARAT - Andy Kurniawan; Siti Nurjannah Nurjannah; Sabaruddin; Adriani; Nurfadhilah Arif (Universitas Muhammadiyah Palembang, 2024)
Indonesia has a high level of plant species diversity and can be utilized by the community. The utilization of these plants has not been widely used by the community in North Maluku, therefore it is important to socialize activities to the community in order to increase public knowledge about multipurpose plants. The service activity was carried out in May 2024. The service participants were community members from Bangko Hamlet, Dodinga Village, West Halmahera Regency. Service activities are carried out by presenting material and providing plant seeds to the community. There are seven types of multipurpose plants socialized, namely ginger (Zingiber officinale), turmeric (Curcuma domestica), lemongrass (Cymbopogon nardus), galangal (Alpinia galanga), galangal (Kaempferia galanga), celery (Apium graveolens), and blustru (Luffa cylindrica). To determine the level of community knowledge about multipurpose plants, pre-test and post-test activities were carried out. The results of the community service activities are that the community recognizes and can plant multipurpose plants in the yard and yard, and can utilize them sustainably.